Gabon Civil Registration and Vital Statistics and Unique Identification Number Systems for Universal Health Coverage : A Case Study - Sahli-Majira, Karine; Haazen, Dominic S.; Togonou, Mahussi Hippolyte; Rassekh, Bahie Mary; Mills, Samuel (World Bank, Washington, DC, 2019)
Gabon’s national health insurance program (Caisse National d’Assurance Maladie et de Garantie Sociale [CNAMGS]) coupled with medical coverage financing for the poorest has helped advance achievement of universal health coverage. In 1975, the National Social Security Fund (NSSF) was created in Gabon to guarantee the social protection of the population and enable financial contributions according to means, and benefits according to needs. In 2007, reforms of Gabon’s health financing system were instituted, including implementation of compulsory health insurance schemes through the CNAMGS. The responsibilities of the NSSF were transferred to the CNAMGS, which provides medical, maternity, and miscellaneous insurance and retirement pensions to insured persons and their dependents. In 2008, Gabon introduced an innovatively financed fund dedicated to the poor that extended health protection to economically disadvantaged Gabonese. The fund is managed by the same public institution that manages the private and public national health insurance schemes, enabling the poorest to have greater access to health services and better financial protection against health risks. The CNAMGS assigns an identification number to each insured individual, although this number does not have all the characteristics of a unique identification number (UIN). The assignment of a UIN at birth would allow linkage of the civil registration, vital statistics, and national identification systems, facilitating coordination between sectors and enabling individuals’ greater access to and efficiency in using services. Gabon is working to strengthen its national health information system (NHIS), to improve health system planning, resource management, and quality of care. By connecting all actors in the health system through information and communication technologies, the integrated NHIS will allow the sharing of health information, statistical data, and human and material resources.